2014
DOI: 10.14348/molcells.2015.02101
|View full text |Cite
|
Sign up to set email alerts
|

14-3-3ζ Regulates Immune Response through Stat3 Signaling in Oral Squamous Cell Carcinoma

Abstract: Ectopic expression of 14-3-3ζ has been found in various malignancies, including lung cancer, liver cancer, head and neck squamous cell carcinoma (HNSCC), and so on. However, the effect of 14-3-3ζ in the regulation of interactions between tumor cells and the immune system has not been previously reported. In this study, we aimed to investigate whether and how 14-3-3ζ is implicated in tumor inflammation modulation and immune recognition evasion. In oral squamous cell carcinoma (OSCC) cell lines and cancer tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Previous studies have suggested the oncogenic roles of 14-3-3ζ in diverse cancer types including HCC 17 , 18 . For example, 14-3-3ζ was upregulated in HCC and can promote HCC invasion and metastasis through binding to AXL (activity of the receptor tyrosine kinase Axl) 9 or through interacting with αB-crystallin mediated by TGF-β and ERK signaling pathways 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested the oncogenic roles of 14-3-3ζ in diverse cancer types including HCC 17 , 18 . For example, 14-3-3ζ was upregulated in HCC and can promote HCC invasion and metastasis through binding to AXL (activity of the receptor tyrosine kinase Axl) 9 or through interacting with αB-crystallin mediated by TGF-β and ERK signaling pathways 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of YWHAZ could mimic all the functions of miR-451 overexpression. YWHAZ plays a critical role in signaling transduction through interaction with target proteins via phosphorylation motif [43] or directly regulating phosphorylation [44, 45]. We identify that forced expression of miR-451 or knockdown of YWHAZ or c-Myc result in decreased p-AKT levels in AML.…”
Section: Discussionmentioning
confidence: 99%
“…59 ), HNRNPA2B1 (ref. 60 ) and YWHAZ 61 . In conclusion, our proteome analysis verifies the induction of an appropriate host response in SARS-CoV-2-infected Huh7 cells and further supports an important role for IFN and MAPK signalling in SARS-CoV-2 infection.…”
Section: Biological Functions Of Sars-cov-2 Rna-binding Proteinsmentioning
confidence: 99%